Hog: handling HDL repository on git. (1st April 2022) - Biesuz, N.V.; Cieri, D.; Giangiacomi, N.; Gonnella, F.; Peck, A.
Abstract: Handling HDL project development within large collaborations presents many challenges in terms of maintenance and versioning, due to the lack of standardised procedures. Hog (HDL on git) is a tcl-based open-source management tool, created to simplify HDL project development and management by exploiting git and Gitlab Continuous Integration (CI). Hog is compatible with the major HDL IDEs from Xilinx and Intel-FPGA, and guarantees synthesis and placing reproducibility and binary file traceability, by linking each binary file to a specific git commit. Hog-CI validates any changes to the code, handles automatic versioning and can automatically simulate, synthesise and build the design.